Óleos essenciais e película à base de fécula de mandioca no controle da antracnose em manga - Alves, Elícia Trindade (2015)
Anthracnose is the main postharvest disease for mango fruits. Limiting to exportation, it is responsible for considerable losses. The struggle to control this plant pathogen by means of alternative methods is constant. Therefore, this research had the objective of evaluating the potential of the film made of cassava starch at 2% and 3%, associated or not to five essential oils obtained from mango postharvest conservation, and the in vitro and in vivo control of an isolate. The isolate obtained from “Tommy Atkins” mango was identified and incorporated to the Mycological Collection of Lavras from the Department of Phytopathology of the Universidade Federal de Lavras (UFLA), in Lavras, Minas Gerais, Brazil. The essential oils obtained from Cymbopogon martinii, Sizirgum aromaticum, Thymus vulgaris, Cinnamomum casia e Cymbopogon citratus were used at 1000 μL.L-1 and were attained from Lazlo company, and selected according to their pathogen inhibition potential. In the in vitro experiments, we evaluated the germination inhibition potential and mycelia growth of the film, combined or not to the oils. In the in vivo experiment, the same treatments were applied to the fruits after the inoculation, evaluated daily until the eighth day, when samples were taken for Scanning Electron Microscopy and epifluorescence. Cinnamon essential oil and the fungicide used inhibited conidia germination, showing the protective effect of this oil. Clove oil, associated or not to the film at 2% and 3%, as well as thyme oil and the fungicide, reduced Mycelial Growth Velocity Index. In the in vivo experiments, all treatments with isolated film, associated or not to the essential oils, presented reduction of injury development (area under the disease progress curve) caused by the fungi inoculated to the fruits, evaluated by both methods. Microscopy has fundamental importance on the visualization of the results.